Tailoring a One Health course for an established non-One Health graduate program in Brazil - Magalhaes, Tereza; Barreto, Ana; Mesquita-Silva, Jamerson; Serravalle, Kamile M. L.; Valente de Andrade, Marcela; Gomes, Rita C. L.; Nazaré, Romero J.; Calado, Rosa M. G. A.; Ribeiro, Guilherme S.; Kitron, Uriel (Frontiers in Tropical Diseases, 2024)
We present a study of the tailoring of a One Health course for its integration into a non-One Health established graduate program at a large public university in Brazil. We highlight important features of the customized syllabus and share some points of discussions that occurred during classes. This information may be valuable to others wishing to design One Health courses for implementation in diverse settings, with the ultimate goal of propagating the concepts, fostering discussions, and facilitating the development and implementation of One Health approaches in groups not usually exposed to this concept.We present a study of the tailoring of a One Health (OH) course for its integration into an established non-OH graduate program at a large public university in Brazil. The graduate program focuses on topics such as environmental resource management, impacts on ecosystems, precariousness of the work environment and relationships, workers' health, social determinants of health, and public policies. Tailoring the OH syllabus involved addressing broader OH concepts, condensing or adapting aspects of infectious diseases, covering noninfectious disease OH topics, and linking OH aspects to ongoing projects in the program.Despite the small class size, students brought diverse backgrounds, significantly enriching discussions. The course was offered in a longer (51 contact hours) and a shorter format (34 contact hours), both of which worked well within a lecture-and discussion-based structure. The extended format allowed more time for student activities and in-depth discussions. The multisectoral and transdisciplinary nature of lectures played a critical role in the course's success. This information may prove valuable for those designing OH courses for implementation in diverse settings, with the ultimate goal of disseminating OH concepts, fostering discussions, and facilitating the development and implementation of OH approaches in groups not typically exposed to this concept.